Analysing the impact of capital structure on bank’s financial performance in Zimbabwe - Machingaifa, Perditah (Midlands State University, 2019)
This research seeks to examine the impact of capital structure on bank’s financial performance in Zimbabwe. The study employed a sample size of ten banks over the period 2013-2017. In conducting this research, the researcher used a mixed approach that was both qualitative and quantitative. Data was collected through audited financial statements and interviews. Quantitative and qualitative methods of data analysis were used that was descriptive statistics, correlation, regression techniques and conclusions of uniform patterns of the data. The result reveals that capital structure measured by debit-equity ratio has negative relationship with financial performance measured by ROA and ROE and capital structure measured by equity multiplier has weak positive influence on financial performance. Subsequently, the researcher recommends that banks should not rely on debt financing but to strike a balance between their choices of capital structure